Respostas

A melhor resposta!
  • Usuário do Brainly
2014-06-09T18:16:24-03:00
A) 5 - 2 . (y - 1) = y + 4 . (- 2 + 3y)

5 - 2 . (y - 1) = y + 4 . (- 2 + 3y)
5 - 2y + 2 = y - 8 + 12y
- 2y - y - 12y = - 8 - 5 - 2
- 15y = - 15 . (- 1)
15y = 15
y = 15/15
y = 1

B) 2 . (x - 3) + 4 . (2x + 1) = 8 - 5 . (x - 4)

2 . (x - 3) + 4 . (2x + 1) = 8 - 5 . (x - 4)
2x - 6 + 8x + 4 = 8 - 5x + 20
2x + 8x + 5x = 8 + 20 + 6 - 4
15x = 30
x = 30/15
x = 2

C) - 2 . (3x - 4 - x) = 26 - 7x

- 2 . (3x - 4 - x) = 26 - 7x
- 6x + 8 + 2x = 26 - 7x
- 6x + 2x + 7x = 26 - 8
3x = 18
x= 18/3
x = 6

D) - (4 - 6x) = - 4 . (1 - x)

- (4 - 6x) = - 4 . (1 - x)
- 4 + 6x = - 4 + 4x
6x - 4x = - 4 + 4
2x = 0
x = 0/2
x = 0
1 5 1